Muscle strength particularity of Grand Tour cyclists from knee isokinetic assessment - Dauty, M.; Menu, P.; Mesland, O.; Fouasson-Chailloux, A. (Science & Sports, 2020)
Objectives: To take part in a Grand Tour, the selection of the cyclists is not easy despite a link between isokinetic knee muscle strength and sprinting power. This study aimed to measure knee muscle strength among professional cyclists and to explore the difference in lower limb force between the rouleur/sprinter and the puncher/climber cycling tactic profiles.